Transcriptome Analysis Reveals the Molecular Mechanism Involved in Carotenoid Absorption and Metabolism in the Ridgetail White Prawn Exopalaemon carinicauda - Yumin Han; Yang Yu; Chengsong Zhang; Shihao Li; Jianbo Yuan; Fuhua Li (Animals)
Astaxanthin plays a vital role in pigmentation, immune function, reproduction, and antioxidation in aquatic species. To clarify the molecular mechanism of astaxanthin utilization in Exopalaemon carinicauda (E. carinicauda), we conducted a comparative transcriptome analysis on the intestine, hepatopancreas, and muscle of E. carinicauda, fed with an astaxanthin diet and a normal diet. A total of 144 differentially expressed genes (DEGs) were identified in three tissues between the two groups. Genes related to absorption and transport, such as LDLR and the vitellogenin receptor, were upregulated in the intestine after astaxanthin supplementation, while the ileal sodium/bile acid cotransporter-like gene was downregulated. In the hepatopancreas, genes involved in lipid storage and degradation were significantly altered at the transcriptional level, including Kruppel 1-like, ACSBG2, δ(7)-sterol 5(6)-desaturase-like, and PNLIPRP2. In the muscle, the expression of the FABP gene was significantly upregulated, while several actin and troponin genes were significantly downregulated. Furthermore, GSEA analysis on the transcriptomes of three tissues revealed that astaxanthin supplementation influenced the expression of genes related to antioxidation and growth, indicating that astaxanthin may have a positive impact on the growth, development, and resistance of organisms. The data from this research provide valuable insights into elucidating the molecular mechanisms underlying astaxanthin absorption and metabolism and also offer guidance for the application of astaxanthin in the aquaculture of economically important crustaceans.